Australia : Information Note on Fiscal Data. (IMF Staff Country Reports; Country Report ;, 2006)
The Australian government registered strong financial performance during the period under review. There was an increase in net worth owing to transactions, as measured by the net operating balance (NOB). These resources enabled the government to reduce its net liabilities and, to a lesser extent, acquire financial assets on a net basis. The Australia pilot study is considered a point of reference for other pilot studies implementing the Government Finance Statistics Manual 2001 framework, as a means of strengthening fiscal analysis.